Managing the returning foreign terrorist fighters and their families: Malaysian experience - Muhammad Uthman El-Muhammady, Ahmad El-Muhammady (The International Centre for Counter-Terrorism (ICCT), 2023)
The main objective of the article is to explore Malaysia’s approach in managing the returning fighters and their families in the post-IS phase. In doing so, the article is divided into four parts. The first part provides the background to Malaysians involvement as foreign fighters starting from the 1990s until the IS case. Second part highlights the uniqueness of IS’ foreign fighters and why Malaysia adopted repatriation policy towards its citizens who involved in IS struggle. The third part explores the process of repatriation of foreign fighters and their families namely the assessment, rehabilitation, prosecution and reintegration. The last part of the article provides an assessment on Malaysia’s approach particularly from the perspective of human rights and rule of law, as well as its overall effectiveness.